A Marxist Analysis of Economic Rights Disputes in Industrial Design: A Case Study of Decision No. 76/Pdt.Sus-Desain Industri/2023/PN.Niaga.Jkt.Pst and Supreme Court Ruling No. 266 K/Pdt.Sus-HKI/2024 on the “Suitcase Generator” - Tommy Arnold; Diana R. W. Napitupulu (Inovasi Pratama Internasional. Ltd, 2025)
The objective of this study is to analyze the industrial design dispute between CV. Rajawali Diesel and Tommy Admadiredja (Decision No. 76/Pdt.Sus-Desain Industri/2023/PN.Niaga.Jkt.Pst) through the lens of Karl Marx’s theory. This case, centered on a claim for damages following the cancellation of an industrial design right, serves as an ideal case study to examine how law functions as a superstructure shaped by the capitalist economic base. The analysis reveals that the Industrial Design Law operates as an instrument to create and protect private property rights (exclusive monopolies), which are foundational to capitalist relations of production. Furthermore, the court’s decision to dismiss CV. Rajawali Diesel’s claim on formal-legal grounds specifically the lack of legal standing demonstrates how the legal superstructure prioritizes legal certainty and formalism essential for capital accumulation, often at the expense of substantive justice for the materially disadvantaged party. This ruling illustrates the ideological function of law, which presents itself as a neutral entity while in reality perpetuating and reproducing the interests of the dominant class by safeguarding market mechanisms and property rights.